BETWEEN THE WEST AND THE EAST: UKRAINIAN ECONOMIC THOUGHT AS THE CROSSROADS - A. Oleinik (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Ukrainian economists, similarly to Ukrainian society, are in the middle of the process of turning from the East to the West. However, the visibility of their work remains low both in the East and the West. The analysis of their publication activity (using data from the Web of Science and eLibrary) confirms these assumptions. It is argued that the first step in this eventual transition consists in building the space for economic debates at the national level. Active and healthy debates at the national level will increase chances of Ukrainian economists to be heard internationally.